Analyzing high school students’ reasoning about electromagnetic induction - Katarina Jelicic; Maja Planinic; Gorazd Planinsic (Physical Review Physics Education Research, 2017)
Electromagnetic induction is an important, yet complex, physics topic that is a part of Croatian high school curriculum. Nine Croatian high school students of different abilities in physics were interviewed using six demonstration experiments from electromagnetism (three of them concerned the topic of electromagnetic induction). Students were asked to observe, describe, and explain the experiments. The analysis of students’ explanations indicated the existence of many conceptual and reasoning difficulties with the basic concepts of electromagnetism, and especially with recognizing and explaining the phenomenon of electromagnetic induction. Three student mental models of electromagnetic induction, formed during the interviews, which reoccurred among students, are described and analyzed within the knowledge-in-pieces framework.